Toward Best Practices for Controlling Mammalian Cell Culture Environments - Klein, Shannon G.; Steckbauer, Alexandra; Alsolami, Samhan M.; Arossa, Silvia; Parry, Anieka J.; Li, Mo; Duarte, Carlos M. (Frontiers in Cell and Developmental Biology, 2022)
The characterization, control, and reporting of environmental conditions in mammalian cell cultures is fundamental to ensure physiological relevance and reproducibility in basic and preclinical biomedical research. The potential issue of environment instability in routine cell cultures in affecting biomedical experiments was identified many decades ago. Despite existing evidence showing variable environmental conditions can affect a suite of cellular responses and key experimental readouts, the underreporting of critical parameters affecting cell culture environments in published experiments remains a serious problem. Here, we outline the main sources of potential problems, improved guidelines for reporting, and deliver recommendations to facilitate improved culture-system based research. Addressing the lack of attention paid to culture environments is critical to improve the reproducibility and translation of preclinical research, but constitutes only an initial step towards enhancing the relevance of in vitro cell cultures towards in vivo physiology.